The Problems of Implementation the Pancasila Student Profile Strengthening Project (P5) in Elementary School - Bahraini, Bahraini; Hanifa, Hanan; Dera Putri , Meysa; Ningsih, Yarisda; Azmi Alwi, Nur (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
The Indonesian education system currently uses the independent curriculum. Project-based learning is implemented in the independent curriculum. In the independent curriculum, learning is emphasized on character development or the profile of Pancasila students, which aims to form competent student characters according to the Pancasila values ??taught in the project-based student profile. The Pancasila student profile is devoted to God, has noble character, Bhinneka Tunggal Ika (Unity in Diversity), mutual cooperation, independence, the ability to think critically, creatively and innovatively, and democracy. This study aims to determine the analysis of obstacles to the implementation of the Pancasila student profile strengthening project (P5) in elementary school education units in the era of the independent curriculum. This study uses a qualitative research type with a literature study method or literature review. The results of the study, the obstacles that occurred during the Pancasila student profile strengthening project (P5) were the lack of understanding of educators or teachers about P5 so that the P5 project was less than optimal. The second obstacle was the lack of support from schools such as the lack of supporting tools for P5 activities and lack of funding. Furthermore, the obstacles that often occur are the lack of active involvement of students in implementing projects to strengthen the profile of Pancasila students and many students are lazy to participate in P5.